A new focus of spotted fever caused by Rickettsia parkeri in Brazil - Nicole Oliveira de Moura Martiniano; Tayra Pereira Sato; Vinicius Figueiredo Vizzoni; Sheila de Figueiredo Ventura; Stefan Vilges de Oliveira; Marinete Amorim; Gilberto Salles Gazêta (Revista do Instituto de Medicina Tropical de São Paulo, 2022)
ABSTRACT Spotted fever (SF) is a tick-borne zoonosis caused by bacteria of the genus Rickettsia . The disease varies in severity from mild clinical forms to severe cases. In Brazil, Rickettsia rickettsii SF is the most serious rickettsiosis and can result in death if not diagnosed and treated at the onset of symptoms. The SF mild form is caused by Rickettsia parkeri strain Atlantic Rainforest, and this etiological agent has been reported in the South, Southeast and Northeast regions of the country, in areas of preserved or little antropized Atlantic Rainforest. Amblyomma ovale is the proven vector and dogs are the hosts associated with the bioagent cycle. During a SF case investigation in Paraty municipality, Rio de Janeiro State, an Atlantic Rainforest biome area in Southeastern Brazil, the human pathogen R. parkeri strain Atlantic Rainforest was detected by PCR in a sample of human skin inoculation eschar and in a female A. ovale tick collected from a dog. These results expand the known area of occurrence of this mild form rickettsiosis in Brazil. In addition, the results of the present study indicate the importance of implementing programs to control canine ectoparasites and to raise awareness of the risks of infection, signs and symptoms of SF caused by R. parkeri strain Atlantic Rainforest.